Trained to teach : a study of women teachers currently not teaching : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Aldridge-Sutton, Jacque (Massey University, 1982)
This study had two main objectives: 1. To describe the population of nonteaching female primary school teachers in terms of demographic and professional variables. 2. To explore the conditions under which these women might return to teaching. To achieve the above objectives, a nation-wide, randomly-selected sample of 110 nonteaching female primary school teachers was sent a self-administered postal questionnaire. There were 79 usable responses, and the data from these forms the basis of this report. The findings of this study indicate that nonteaching female primary school teachers fall into three distinct groups. One group is comprised of female teachers who do not want to teach ever again. As a group, they are older, their children are older, and they have given more years of service than women in the other two groups. As well, those of them who are not in the paid workforce do not intend to return to paid employment. As a group they represent about a quarter of the sample. About ten percent of the sample intend to return to teaching. They have young children and had left the classroom to be at home with their children. These women are generally under 35 years of age, and their children of preschool or early primary school, age. They indicated that they would return to the classroom when their children are older. The third group of teachers comprising about two thirds of the sample, are of the opinion that it is possible that they may return to teaching. They too have husbands and young children, but many of them feel unsure about a return to any paid work. Respondents were asked why they are not currently teaching, and the great majority indicated a strong commitment to the roles of wife. They did not want to take any employment which would interfere with their fulfilment of these roles. Generally, the women in this study liked teaching, particularly the involvement with children and the fostering of their development. An important outcome of the study is the advancement of a theory of commitment, in which people are seen to commit themselves to certain values. These values may be expressed in many different lifetasks. The women in this study liked the nurturant role in teaching, and once they had their own children they felt that the needs of these children of theirs should come before other considerations.
Keywords: New Zealand Women teachers; Retired teachers